Fiqh muqaran - Amram, Adriana Izzah; Bakri, Husna Najihah; Mohd Salehudin, Mardiyyah Mutmainnah; Abdul Hamid @ Sulaiman, Nur Aina Adlina; Hanapi, Nureen Hafiza (2025)
Slide presentation for "Fiqh muqaran"